Revitalización paisajística urbana. Aprovechamiento de las Rondas hídricas del zanjón Mirriñao en Palmira, Valle del Cauca (2020)
Lacking adequate treatment for water and the arboreal spot, the green areas that the ecosystem has become a focus of residual areas, generating an environmental problem of great impact for the city; the lack of regularization of the protection bands makes them vulnerable to the loss and uncontrolled growth of housing areas that violate the characteristics of the natural landscape vital for the development of life and urban dynamics. The public space of protection is a strategy that arises through the project response to the needs of the city and landscape revitalization of the zanjones urban, which should be a priority for the development of the city, taking into account this green axis as an element articulator of city and incidiendo in the recovery of the ecosystem by means of architectonic urban actions for the treatment of the zone.